Performance of point‐of‐care Xpert HIV‐1 plasma viral load assay at a tertiary HIV care centre in Southern India. Issue 10 (October 2017) - Swathirajan, Chinnambedu Ravichandran; Vignesh, Ramachandran; Boobalan, Jayaseelan; Solomon, Sunil Suhas; Saravanan, Shanmugam; Balakrishnan, Pachamuthu
Abstract : Background. : Sustainable suppression of HIV replication forms the basis of anti‐retroviral therapy (ART) medication. Thus, reliable quantification of HIV viral load has become an essential factor to monitor the effectiveness of the ART. Longer turnaround‐time (TAT), batch testing and technical skills are major drawbacks of standard real‐time PCR assays. Methods. : The performance of the point‐of‐care Xpert HIV‐1 viral load assay was evaluated against the Abbott RealTime PCR m2000rt system. A total of 96 plasma specimens ranging from 2.5 log10 copies ml ‐1 to 4.99 log10 copies ml ‐1 and proficiency testing panel specimens were used. Precision and accuracy were checked using the Pearson correlation co‐efficient test and Bland‐Altman analysis. Results. : Compared to the Abbott RealTi m e PCR, the Xpert HIV‐1 viral load assay showed a good correlation (Pearson r=0.81; P <0.0001) with a mean difference of 0.27 log10 copies ml ‐1 (95 % CI, −0.41 to 0.96 log10 copies ml ‐1 ; sd, 0.35 log10 copies ml ‐1 ). Conclusion. : Reliable and ease of testing individual specimens could make the Xpert HIV‐1 viral load assay an efficient alternative method for ART monitoring in clinical management of HIV disease in resource‐limited settings. The rapid test results (less than 2 h) could help in making an immediate clinical decision, which further strengthens patient care.